Pengaruh Tegangan Listrik dan Arus Listrik terhadap Kinerja Termoelektrik Sebagai Pendingin Termoelektrik - Oktabiansyah, Tobi; Rifky (METALIK : Jurnal Manufaktur, Energi, Material Teknik, 2023)
Thermoelectric material is a material that has thermal and electrical properties. The thermoelectric module can function as an electric generator, heat pump and cooler. The thermoelectric modules used in this study are the TEC 1-12706 type and the TEG SP 1848 type. This study uses both of these modules with each module using four thermoelectrics to be used as a cooling system. The purpose of the research is to obtain the lowest temperature on the cold side and the highest CoP thermoelectric performance coefficient on the two different modules with variations in the size of the electric voltage and electric current that have been determined, then to get a thermoelectric module that has a higher performance coefficient of the two types of thermoelectric modules used. used. The research method used is experimental. The two modules are separately supplied with DC electrical energy so that heat is absorbed on the cold side and heat is released on the hot side so that a temperature difference occurs, and an aluminum heatsink is attached to the cold side and the hot side. The data obtained from the input data are ambient temperature, electric voltage, and electric current. Then what is obtained from the output data is the temperature of the hot side, the temperature of the cold side, and the temperature of the cold room. The results of the study on the TEC 1-12706 module with variations in electric voltage produce a minimum cold side temperature of 5.9°C with the highest CoP value of the cooling system of 0.1821, while variations in electric current produce a minimum cold side temperature of 8.0°C with the highest CoP value of the cooling system of 0.3247. For the TEG SP 1848 module, variations in electric voltage produce a minimum cold side temperature of 8.3°C with the highest CoP value of the cooling system of 0.2371, while variations in electric current produce a minimum cold side temperature of 11.1°C with a CoP value the highest cooling system is 0.2158. Thus this study achieved the result that the use of the TEC 1-12706 module with variations in electric voltage produced the lowest temperature of 5.9 oC. While the use of TEC 1-12706 with variations in electric current produces the highest CoP value of 0.3247. There for the TEC 1-12706 module has a higher performance than the TEG SP 1848 module in terms of the lowest temperature achievement and the highest CoP value.